Analisis Pengaruh Faktor-Faktor Kualitas Pelayanan terhadap Kepuasan Pasien (Studi Kasus pada Puskesmas Bangetayu Semarang) - Wahyuningsih, Susanti; Kurniawati, Endang; Hermawati, Charoeina Eka (STIE PENA, 2024)
The purpose of this study was to determine the influence of service quality factors on patient satisfaction at the Bangetayu Health Center in Semarang. The method used in this study is the Berganda Regression Analysis. The population in this study were patients at Bangetayu Health Center, Semarang. The sample for this study was 99 people using the Proportional Random Sampling technique, namely taking samples by giving the same fourthness to members of the population. The data collection method is through questionnaires distributed to Bangetayu Semarang Health Center patients. The type of data used is primary and secondary data. The results of this study indicate that Tangible has no significant effect on patient satisfaction as indicated by a significance level of 0.310 > 0.05 and tcount 1.021